Displacement controlled rocking behaviour of rigid objects. - Kafle, Bidur
The capacity of a gravity structure to counter seismically induced overturning can only be estimated with good accuracy using a dynamic analysis of the rotational (rocking) motion involving large displacement theory. Seismic assessment employing quasi-static analysis can be overly conservative if the reserve theory. Seismic assessment employing quasi-static analysis can be overly conservative if the reserve capacity of this type of rocking structure to displace without overturning is not taken into account. It was revealed through dynamic testing on a shaking table that the overturning hazards of ground shaking are best represented by the peak displacement demand (PDD) parameter and that the vulnerability to overturning instability decreases with the increasing size of the object when the aspect ratio is held constant. This finding has important implications on the engineering of structures for countering moderate ground shaking in regions of low and moderate seismicity. Experimental data were validated and supplemented by computer simulations that involved generating artificial acceleorgrams of designated earthquake scenarios and non-linear time history analyses of the overturning motions. Based on these simulations, fragility curves were constructed for estimating the probability of overturning for given levels of PDD and for different specimen dimensions. An expression was developed for estimating the level of PDD required to overturn rectangular objects of given dimensions for 5 percent probability of exceedance.
Keywords: Overturning; Rocking; Displacement controlled behaviour; Shaking table; Fragility curves